Evaluation of diagnostic characters of the Tanytarsus chinyensis group (Diptera: Chironomidae), with description of a new species from Lapland - Giłka, Wojciech; Paasivirta, Lauri (Zootaxa, 2009)
Tanytarsus salmelai sp. n. collected from the northernmost sites of the Finnish Lapland is described. The new species and two sibling Tanytarsus, T. brundini Lindeberg, 1963 and T. curticornis Kieffer, 1911, are compared, diagnosed and illustrated in detail. Morphological variability and diagnostic characters of the three related species are discussed. An emended diagnosis for adult males of the Tanytarsus chinyensis species group and a key to determination of European species of the group are also provided.